Use of AI in institutional provision of state housing programs. Foreign experience and possibilities of application in Ukraine - ZELTSER, Yevgen (Ways to Improve Construction Efficiency, 2025)
The need to provide housing for Ukrainian citizens has been acute since Ukraine gained independence. This problem has become even more urgent since the beginning of hostilities. The total amount of direct damage caused to Ukraine's infrastructure as a result of Russia's full-scale invasion has reached almost $170 billion. This figure has increased by $12.6 billion since the beginning of 2024, reflecting further destruction from missile attacks and hostilities. The largest losses were suffered by housing, transport infrastructure and energy. The residential sector remains the most affected - direct losses are estimated at $60 billion. As of November 2024, 236 thousand residential buildings have been damaged or destroyed, of which 209 thousand are private houses, 27 thousand are apartment buildings and another 600 are dormitories. Under such conditions, state policy measures aimed at developing and reforming state housing programs become particularly relevant, which should take into account existing global experience in providing citizens with housing, in particular the use of artificial intelligence (AI) in the institutional provision of state housing programs. AI is now becoming a key tool in modernizing public housing programs, especially in the face of growing demand for social and affordable housing. The use of AI allows for improved resource allocation accuracy, prevention of corruption schemes, and automation of bureaucratic procedures. Many countries are already using machine learning algorithms to predict housing needs, optimize financing and increase transparency in processes. In Ukraine, the problem of providing housing is especially relevant for internally displaced persons, socially vulnerable citizens, and youth, so the introduction of modern technologies is an urgent necessity. AI can significantly improve the management of public housing programs by increasing the efficiency of processes, ensuring transparency and optimizing resource allocation. The article is devoted to studying the possibilities of using AI in the institutional provision of state housing programs, studying foreign experience and assessing the prospects for its application in Ukraine. The effectiveness of modern digital tools in the process of managing public housing programs and distributing subsidies is analyzed. The benefits of using AI in the public housing sector are investigated. The main barriers to the digitalization of housing policy in Ukraine and ways to overcome them are identified.